Para-aramid coating diaphragm and preparation method thereof
By introducing a para-aramid coating and ceramic coating structure into the diaphragm, the problems of low shrinkage rate and serious edge-curling phenomenon in the prior art are solved, and the mechanical strength of the diaphragm is improved and the edge-curling phenomenon is eliminated at high temperatures.
Patent Information
- Application Number
- CN202510000022.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-01
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-01
AI Technical Summary
The existing aramid-coated diaphragm has a low shrinkage rate at medium temperature, and the coating shrinks due to the lack of support substances, which makes the edge curling phenomenon serious and difficult to deal with.
Using a diaphragm structure including a base film, a para-aramid coating and a ceramic coating, a vapor phase powder and a first ceramic powder are added to the para-aramid coating, and a second ceramic powder is used in the ceramic coating, the ratio of each layer of materials is adjusted to improve the temperature resistance and mechanical strength of the membrane.
It improves the mechanical strength of the diaphragm at high temperature, reduces the fall of inorganic particles on the para-aramid coating, eliminates the phenomenon of diaphragm edge curling, extends the placement time of para-aramid slurry, and enhances the adhesion of the diaphragm.
Smart Images

Figure CN119764743A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery separators, and in particular relates to a para-aramid coating separator and a preparation method thereof. Background Art
[0002] Although the aramid-coated diaphragm has high temperature resistance, its shrinkage rate is worse than that of the ceramic-coated diaphragm at medium temperature (130°C). The main reason is that the aramid-coated diaphragm lacks substances that can support the coating. At 130°C, the PE-based film is in a molten state, and the aramid-coated diaphragm shrinks rapidly. The coating will shrink to a certain extent at 130°C due to lack of support.
[0003] The para-aramid molecular chain of traditional para-aramid (poly(p-phenylene terephthaloyl chloride)) is in a highly straight trans conformation. Due to the conjugation effect between the amide group and the benzene ring, it has a high internal rotation potential energy, and there are a large number of hydrogen bonds between adjacent molecular chains. The aramid molecules are internally rotated together, which makes it difficult to control the viscosity of the slurry; because the attraction between the fibers is relatively strong, when coated on the base film, the stress will be very large, causing the diaphragm to have a very serious warping phenomenon, and it is very difficult to deal with the warping of the diaphragm. There are still many problems with the aramid-coated diaphragms in the prior art. Summary of the invention
[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a para-aramid coated diaphragm.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned para-aramid coated diaphragm.
[0006] The purpose of the present invention is achieved through the following technical solutions.
[0007] A para-aramid coating diaphragm, comprising: a base film, a para-aramid coating and a ceramic coating, wherein the para-aramid coating is connected to one surface of the base film, and the ceramic coating is one layer or two layers;
[0008] When the ceramic coating is a single layer, the ceramic coating is connected to the other side of the base film or to the para-aramid coating;
[0009] When the ceramic coating has two layers, the two ceramic coatings are a first ceramic coating and a second ceramic coating, the first ceramic coating is connected to the para-aramid coating, and the second ceramic coating is connected to the other side of the base film;
[0010] The para-aramid coating comprises: para-aramid (the molecular chain of para-aramid is non-straight chain), gas phase powder and first ceramic powder, and each layer of the ceramic coating comprises: second ceramic powder. In terms of mass fractions, the ratio of para-aramid, gas phase powder, first ceramic powder and second ceramic powder in each layer of the ceramic coating is (1-4): (1-4): (9-21): (40-80).
[0011] When the ceramic coating is a layer and the ceramic coating is directly connected to the base film, the ratio of the para-aramid, the gas phase powder, the first ceramic powder and the second ceramic powder in the ceramic coating is (2-4): (2-4): (17-21): (69-79);
[0012] When the ceramic coating is a layer and the ceramic coating is connected to the para-aramid coating, the ratio of the para-aramid, the gas phase powder, the first ceramic powder and the second ceramic powder in the ceramic coating is (2-4): (2-4): (17-21): (69-79);
[0013] When the ceramic coating is two layers, the two layers of the ceramic coating are a first ceramic coating and a second ceramic coating, the first ceramic coating is connected to the para-aramid coating, and the second ceramic coating is connected to the other side of the base film, and the ratio of para-aramid, gas phase powder, first ceramic powder, second ceramic powder in the first ceramic coating and second ceramic powder in the second ceramic coating is (1-2): (1-2): (9-13): (41-45): (41-44).
[0014] In the above technical solution, the gas phase powder is a mixture of one or more of gas phase aluminum oxide, gas phase silicon dioxide and gas phase barium titanate.
[0015] In the above technical solution, the first ceramic powder is a mixture of one or more of aluminum oxide, lithium aluminum titanium phosphate, boehmite and barium sulfate.
[0016] In the above technical solution, the second ceramic powder is a mixture of one or more of alumina, lithium aluminum titanium phosphate, boehmite and barium sulfate, and the particle size D90 of the second ceramic powder is ≤1.5 μm.
[0017] In the above technical solution, the thickness of the para-aramid coating is 1 to 3 μm.
[0018] In the above technical solution, the thickness of each ceramic coating layer is 1 to 3 μm.
[0019] The method for preparing the above-mentioned para-aramid coated diaphragm comprises: first coating a ceramic slurry and then drying to form the ceramic coating, and then coating a para-aramid slurry, extracting to form pores, and finally drying to form a para-aramid coating, wherein the ceramic slurry comprises: water, a dispersant, a second ceramic powder, a thickener, a gas-phase pore former and a binder, and the thickener is an aqueous solution of sodium carboxymethyl cellulose; in the ceramic slurry: in terms of mass fractions, the ratio of the water, the dispersant, the second ceramic powder, the sodium carboxymethyl cellulose, the gas-phase pore former and the binder in the thickener is (15-22): (3-4): (28-35): (2-5): (3-6): (2-8), and the gas-phase pore former is isopropanol;
[0020] The para-aramid slurry comprises: gas phase powder, first ceramic powder and para-aramid, and the ratio of the gas phase powder, the first ceramic powder and the para-aramid is (1-4): (9-21): (1-4) by weight.
[0021] In the above technical solution, the para-aramid slurry also includes calcium chloride, and the ratio of gas phase powder to calcium chloride is (1-3): (0.5-1) by mass.
[0022] In the above technical solution, the para-aramid slurry also includes a solvent, and the solid content of the para-aramid slurry is 3-8wt%.
[0023] In the above technical solution, the concentration of sodium carboxymethyl cellulose in the aqueous solution of sodium carboxymethyl cellulose is 1 to 5 wt %.
[0024] In the above technical solution, the dispersant is sodium polyacrylate.
[0025] In the above technical solution, the adhesive is a methacrylate adhesive.
[0026] The preparation method of the ceramic slurry comprises: mixing water, a dispersant, a second ceramic powder, a thickener, a gas-phase pore-forming agent and a binder until they are uniform to obtain the ceramic slurry.
[0027] The preparation method of the ceramic slurry comprises: mixing water and a dispersant until uniform, adding a second ceramic powder, mixing until uniform, adding a thickener, mixing until uniform, adding a gas phase pore former, mixing until uniform, and finally adding a binder, mixing until uniform to obtain a ceramic slurry.
[0028] In the preparation method of ceramic slurry, water and dispersant are mixed, stirred for 10 to 20 minutes until uniform, the second ceramic powder is added, stirred for 2 to 3 hours, sand milled for 20 to 30 minutes until uniform, thickener is added, stirred for 10 to 20 minutes until uniform, gas phase pore forming agent is added, stirred for 10 to 20 minutes until uniform, and finally a binder is added, stirred for 10 to 20 minutes until uniform, to obtain ceramic slurry. The preparation method of the above-mentioned para-aramid slurry includes: mixing gas phase powder, first ceramic powder and first solvent until uniform to obtain A solution, mixing A solution and para-aramid polymer solution until uniform to obtain para-aramid slurry, and the para-aramid polymer solution includes: para-aramid and calcium chloride.
[0029] In the above technical solution, the ratio of the gas phase powder, the first ceramic powder and the para-aramid in the para-aramid polymer solution is (1-4): (9-21): (1-4) by mass.
[0030] In the above technical solution, the viscosity of the para-aramid polymer solution is 800-3000CP.
[0031] In the above technical solution, the first solvent is N-methylpyrrolidone (NMP) (water content ≤ 0.5wt%), and the ratio of the gas phase powder to the first solvent is (1-5): (90-98) by mass.
[0032] In the preparation method of the para-aramid slurry, the gas phase powder, the first ceramic powder and the first solvent are mixed, stirred for 40 to 80 minutes, and sand-milled for 20 to 30 minutes until uniform, to obtain a solution A.
[0033] In the preparation method of the para-aramid slurry, the A solution and the para-aramid polymer solution are mixed and stirred for 80 to 120 minutes until they are uniform, thereby obtaining the para-aramid slurry.
[0034] In the method for preparing the para-aramid slurry, the rotation speed of the sand mill is 1000-1500 r / min.
[0035] In the preparation method of para-aramid slurry, the method for obtaining para-aramid polymer solution comprises: mixing calcium chloride and a second solvent until uniform, cooling to 5-20°C to obtain a first solution, mixing the first solution, p-phenylenediamine and a modifier until uniform, cooling to -8--2°C to obtain a second solution, spraying molten terephthaloyl chloride into the second solution, stirring while spraying, and stirring at -3-0°C for 1-3h after spraying to obtain a para-aramid polymer solution, wherein, by weight, the ratio of calcium chloride, the second solvent, p-phenylenediamine and the modifier is (2-8): (90-96.4): (2-5): (1-3), the modifier is one or two of 4,4'-diaminodiphenyl ether and 1,3-di(4'-aminophenoxy)benzene, and by weight, the ratio of p-phenylenediamine to molten terephthaloyl chloride is (2-5): (1-3).
[0036] In the method for obtaining para-aramid polymer solution, the injection speed is 0.5 to 1.5 L / min.
[0037] In the method for obtaining a para-aramid polymer solution, the second solvent is N-methylpyrrolidone (NMP) (water content ≤ 0.2 wt %), and the water content of the second solvent is less than that of the first solvent.
[0038] In the method for obtaining the para-aramid polymer solution, terephthaloyl chloride solid is heated to 80-95° C. to obtain molten terephthaloyl chloride.
[0039] In the method for obtaining a para-aramid polymer solution, calcium chloride needs to be calcined at 400-450° C. for 4 hours before being mixed with a second solvent.
[0040] In the method for obtaining the para-aramid polymer solution, calcium chloride and a second solvent are mixed and stirred at 60-90° C. for 6 hours until they are uniform.
[0041] In the method for obtaining the para-aramid polymer solution, the first solution, paraphenylenediamine and a modifier are mixed and stirred at 5 to 20° C. for 3 to 5 hours until the mixture is uniform.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] 1. The para-aramid coating diaphragm of the present invention comprises a base film, a para-aramid coating and a ceramic coating, thereby improving the temperature resistance of the diaphragm. Such a structure enables the para-aramid coating diaphragm of the present invention to maintain a certain mechanical strength at high temperatures. Moreover, after the ceramic slurry is coated on the para-aramid coating, the inorganic particles on the para-aramid coating will be prevented from falling off.
[0044] 2. In order to reduce the hydrogen bonds between aramid molecules during the polymerization of para-aramid, the present invention reduces the use of p-phenylenediamine and uses 4,4'-diaminodiphenyl ether and / or 1,3-di(4'-aminophenoxy)benzene to replace part of the p-phenylenediamine, so that the aramid molecules are partially linked by hydrogen bonds to maintain the rigidity of the aramid molecules, and the viscosity of the para-aramid polymerization liquid can be more controllable, which can greatly extend the placement time of the para-aramid slurry. The para-aramid polymerization liquid of the present invention has a network structure of molecules due to the reduction of hydrogen bonds. After mixing with the gas phase powder and the first ceramic powder, the packaging is more tightly, which can increase the adhesion of the coating and enhance the mechanical strength of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the SEM of the para-aramid coating in the para-aramid coating diaphragm prepared in Example 2;
[0046] Figure 2 This is the SEM of the para-aramid coating in the para-aramid coating membrane prepared in Comparative Example 1. DETAILED DESCRIPTION
[0047] Para-aramid is a polymer with a rigid chain, and the molecular chain is in a highly straight trans conformation. Due to the conjugation effect between the amide group and the benzene ring, it has a very high internal rotation potential, and there are a large number of hydrogen bonds between adjacent molecular chains. During the synthesis process, as the molecular weight increases, a large number of aramid molecules will attract each other due to hydrogen bonds, and the molecules will rotate internally, resulting in a rapid increase in viscosity during polymerization. If not controlled, a gel state or even a solid will be formed in a very short time. The present invention adopts a modifier to change the aramid molecule from a straight chain to a zigzag and chain shape, reduce hydrogen bonds, prevent the aramid molecule from rotating internally, and the viscosity increases slowly during the polymerization process, thereby achieving the purpose of controlling the viscosity of the para-aramid polymer liquid.
[0048] The internal rotation between para-aramid molecules is relatively serious. After extraction and drying, due to the lack of solvent, the aramid molecules shrink rapidly due to the internal rotation force, resulting in a relatively serious diaphragm edge warping phenomenon. The present invention adopts a modifier to reduce the internal rotation of the aramid molecules and the internal rotation force, thereby eliminating the diaphragm edge warping phenomenon.
[0049] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0050] In the following examples, the base film is a PE film, and the thickness of the base film is 9 μm.
[0051] Ionic conductivity: The test temperature is 25°C and the test relative humidity is 30%.
[0052] Diaphragm adhesion: Cut the diaphragm into strips (samples) with a width of 15 mm and a length of 100 mm, and then use 3M tape to bond the side of the diaphragm coated with the para-aramid coating (Comparative Example 3 is "bonding the side of the diaphragm coated with a ceramic coating with 3M tape"). Use a stretching machine to pull the sample and the tape apart. The average force (N) generated by pulling apart divided by the length of the sample (0.1m) is the diaphragm adhesion.
[0053] In the following embodiments, the water content of the second solvent is less than that of the first solvent.
[0054] The solid content of the para-aramid slurry in Example 1 is 3 wt %. The solid content of the para-aramid slurry in Example 2 is 5 wt %. The solid content of the para-aramid slurry in Example 3 is 8 wt %.
[0055] In the following examples, calcium chloride and modifiers were extracted to create pores.
[0056] Example 1
[0057] A para-aramid coating diaphragm comprises a base film, a para-aramid coating and a ceramic coating, wherein the para-aramid coating is connected to one surface of the base film, and the ceramic coating is connected to the para-aramid coating.
[0058] A method for preparing the above-mentioned para-aramid coated diaphragm comprises: using an anilox roller to coat the para-aramid slurry on one side of the base film, extracting (the extraction is sequentially passing through extracting liquids with extractant concentrations from high to low, the extracting liquid is N-methylpyrrolidone (NMP), the extracting liquids with extractant concentrations from high to low are sequentially a first extracting liquid, a second extracting liquid and a third extracting liquid, the first extracting liquid and the second extracting liquid are respectively a mixture of an extracting liquid and deionized water, the third extracting liquid is deionized water, the concentration of the extracting liquid in the first extracting liquid is 90wt%, and the concentration of the extracting liquid in the second extracting liquid is 60wt%), and drying in an oven at 40°C. After drying for 3 minutes, a para-aramid coating with a thickness of 1 μm was obtained on the base film (the para-aramid coating includes: para-aramid, vapor phase powder and first ceramic powder), and ceramic slurry was coated on the para-aramid coating using an anilox roller. After coating, it was directly dried and rolled up in an oven (the oven temperature was 60°C, and the drying time was 15 seconds). A ceramic coating with a thickness of 1 μm was obtained on the para-aramid coating (the ceramic coating includes: second ceramic powder), and a para-aramid coated diaphragm was obtained. The ratio of para-aramid, vapor phase powder, first ceramic powder and second ceramic powder in the ceramic coating was 2:2:17:79 by mass.
[0059] The preparation method of ceramic slurry includes: adding a dispersant to water, stirring for 10 minutes until uniform, adding a second ceramic powder, stirring for 2 hours, sand grinding in a pin-type sand mill for 20 minutes until uniform, adding a thickener, stirring for 10 minutes until uniform, adding a gas-phase pore-forming agent, stirring for 10 minutes until uniform, and finally adding a binder, stirring for 10 minutes until uniform, to obtain a ceramic slurry, wherein the binder is methyl methacrylate, the thickener is an aqueous solution of sodium carboxymethyl cellulose, the concentration of sodium carboxymethyl cellulose in the aqueous solution of sodium carboxymethyl cellulose is 5wt%, the second ceramic powder is aluminum oxide, the particle size D90 of the second ceramic powder is 1.5μm, the dispersant is sodium polyacrylate, the gas-phase pore-forming agent is isopropanol, and the ratio of water, dispersant, second ceramic powder, sodium carboxymethyl cellulose, gas-phase pore-forming agent and binder is 15:3:28:2:3:2 by mass.
[0060] The preparation method of the para-aramid slurry comprises: mixing a gas phase powder, a first ceramic powder and a first solvent, stirring for 40 minutes, sand milling for 20 minutes until uniform (the speed of the sand mill is 1000r / min), obtaining a solution A, adding the solution A to a para-aramid polymer solution (the viscosity of the para-aramid polymer solution is 800CP), stirring for 80 minutes until uniform, and obtaining a para-aramid slurry, wherein the para-aramid polymer solution comprises: para-aramid and calcium chloride, in parts by mass, the gas phase powder The ratio of the first ceramic powder to the para-aramid in the para-aramid polymerization liquid is 1:9:1, the ratio of the gas phase powder to calcium chloride is 1:0.5 by weight, the ratio of the gas phase powder to the first solvent is 1:90 by weight, the first solvent is N-methylpyrrolidone (NMP) (water content ≤0.5wt%), the gas phase powder is gas phase alumina (particle size is 20-60nm), the first ceramic powder is alumina (alumina particle size D90: 0.9μm), and a para-aramid polymerization liquid is prepared. The method comprises: firstly placing calcium chloride in a muffle furnace and calcining at 420° C. for 4 hours, mixing the calcined calcium chloride with a second solvent, stirring at 80° C. for 6 hours until completely dissolved, cooling to 5° C. to obtain a first solution, mixing the first solution, p-phenylenediamine and a modifier, stirring at 5° C. for 3 hours until completely dissolved, cooling to -8° C. to obtain a second solution, and spraying molten terephthaloyl chloride (solid terephthaloyl chloride is added to a tank body and heated to 80° C. to obtain molten terephthaloyl chloride) onto the second solution. The solution is sprayed while stirring (the spraying speed is 0.5 L / min), and then stirred at -3°C for 1 hour after spraying to obtain a para-aramid polymerization solution, wherein the ratio of calcium chloride, the second solvent, p-phenylenediamine and the modifier is 2:96.4:2:1 by weight, the modifier is 4,4'-diaminodiphenyl ether, the ratio of p-phenylenediamine to molten terephthaloyl chloride is 2:1 by weight, and the second solvent is N-methylpyrrolidone (NMP) (water content ≤0.2wt%).
[0061] Example 2
[0062] A para-aramid coating diaphragm comprises a base film, a para-aramid coating and a ceramic coating, wherein the para-aramid coating is connected to one surface of the base film, and the ceramic coating is connected to the other surface of the base film.
[0063] A method for preparing the above-mentioned para-aramid coated diaphragm comprises: using an anilox roller to coat the para-aramid slurry on one side of the base film, extracting (the extraction is sequentially passing through extracting liquids with extractant concentrations from high to low, the extracting liquid is N-methylpyrrolidone (NMP), the extracting liquids with extractant concentrations from high to low are sequentially a first extracting liquid, a second extracting liquid and a third extracting liquid, the first extracting liquid and the second extracting liquid are respectively a mixture of an extracting liquid and deionized water, the third extracting liquid is deionized water, the concentration of the extracting liquid in the first extracting liquid is 80wt%, and the concentration of the extracting liquid in the second extracting liquid is 50wt%), drying at 60°C After drying for 3 minutes, a para-aramid coating with a thickness of 1 μm was obtained on one side of the base film (the para-aramid coating includes: para-aramid, vapor phase powder and first ceramic powder), and the ceramic slurry was coated on the other side of the base film using an anilox roller. After coating, it was directly dried in an oven (the oven temperature was 60°C, and the drying time was 15 seconds) to obtain a ceramic coating with a thickness of 1 μm on the base film (the ceramic coating includes: second ceramic powder), and a para-aramid coated diaphragm was obtained. The ratio of para-aramid, vapor phase powder, first ceramic powder and the second ceramic powder in the ceramic coating was 3:3:19:75 by mass.
[0064] The preparation method of ceramic slurry includes: adding a dispersant to water, stirring for 15 minutes until uniform, adding a second ceramic powder, stirring for 2.5 hours, sand-milling in a pin-type sand mill for 25 minutes until uniform, adding a thickener, stirring for 15 minutes until uniform, adding a gas-phase pore-forming agent, stirring for 15 minutes until uniform, and finally adding a binder, stirring for 15 minutes until uniform, to obtain a ceramic slurry, wherein the binder is methyl methacrylate, the thickener is an aqueous solution of sodium carboxymethyl cellulose, the concentration of sodium carboxymethyl cellulose in the aqueous solution of sodium carboxymethyl cellulose is 5wt%, the second ceramic powder is boehmite, the particle size D90 of the second ceramic powder is 0.8μm, the dispersant is sodium polyacrylate, the gas-phase pore-forming agent is isopropanol, and the ratio of water, dispersant, second ceramic powder, sodium carboxymethyl cellulose, gas-phase pore-forming agent and binder is 18:4:31:4:5:6 by mass.
[0065] The preparation method of the para-aramid slurry comprises: mixing a gas phase powder, a first ceramic powder and a first solvent, stirring for 60 minutes, sand milling for 25 minutes until uniform (the speed of the sand mill is 1300r / min), obtaining a solution A, adding the solution A to a para-aramid polymer solution (the viscosity of the para-aramid polymer solution is 1800CP), stirring for 100 minutes until uniform, and obtaining a para-aramid slurry, wherein the para-aramid polymer solution comprises: para-aramid and calcium chloride, and the gas phase powder, the first ceramic powder and the para-aramid polymer are mixed by weight. The ratio of para-aramid in the mixed liquid is 3:15:3, the ratio of gas phase powder to calcium chloride is 2:0.8 by weight, the ratio of gas phase powder to the first solvent is 3:97 by weight, the first solvent is N-methylpyrrolidone (NMP) (water content ≤0.5wt%), the gas phase powder is gas phase silicon dioxide (average particle size of 15nm), the first ceramic powder is lithium aluminum titanium phosphate (D90: 0.8μm), and the method for preparing the para-aramid polymer solution comprises: firstly putting calcium chloride into a muffle furnace and calcining it at 420℃ for 4h, and then The calcined calcium chloride is mixed with the second solvent, stirred at 80°C for 6 hours until completely dissolved, cooled to 10°C to obtain a first solution, the first solution, p-phenylenediamine and the modifier are mixed, stirred at 10°C for 3 hours until completely dissolved, cooled to -5°C to obtain a second solution, and molten terephthaloyl chloride (solid terephthaloyl chloride is added to a tank and heated to 90°C to obtain molten terephthaloyl chloride) is sprayed into the second solution, stirred while spraying (the spraying speed is 1L / min), and stirred at -1°C for 1 hour after spraying to obtain p-phenylenediamine. Aramid polymerization liquid, wherein, by weight, the ratio of calcium chloride, the second solvent, p-phenylenediamine and the modifier is 5.2:93:3:2, the modifier is 4,4'-diaminodiphenyl ether and 1,3-bis(4'-aminophenoxy)benzene, by weight, the ratio of 4,4'-diaminodiphenyl ether and 1,3-bis(4'-aminophenoxy)benzene is 5:3, by weight, the ratio of p-phenylenediamine and molten terephthaloyl chloride is 3:2, and the second solvent is N-methylpyrrolidone (NMP) (water content ≤0.2wt%).
[0066] Example 3
[0067] A para-aramid coating diaphragm comprises: a base film, a para-aramid coating and a ceramic coating, wherein the para-aramid coating is connected to one side of the base film, the ceramic coating is two layers, the two layers of ceramic coating are a first ceramic coating and a second ceramic coating, the first ceramic coating is connected to the para-aramid coating, and the second ceramic coating is connected to the other side of the base film.
[0068] A method for preparing the above-mentioned para-aramid coated diaphragm comprises: using an anilox roller to coat a para-aramid slurry on one side of a base film, extracting (the extraction is sequentially passing through extracting liquids with extractant concentrations from high to low, the extractant is N-methylpyrrolidone (NMP), the extracting liquids with extractant concentrations from high to low are sequentially a first extracting liquid, a second extracting liquid and a third extracting liquid, the first extracting liquid and the second extracting liquid are respectively a mixture of an extracting liquid and deionized water, the third extracting liquid is deionized water, the concentration of the extracting liquid in the first extracting liquid is 70wt%, and the concentration of the extracting liquid in the second extracting liquid is 40wt%), drying at 80°C for 3min, and obtaining a para-aramid coating with a thickness of 1μm on one side of the base film (the para-aramid coating comprises: para-aramid, gas phase powder and a first ceramic powder), using an anilox roller Ceramic slurry is coated on the para-aramid coating, and the coating is directly dried in an oven (the oven temperature is 60°C, and the drying time is 15s) to obtain a first ceramic coating with a thickness of 1 μm on the para-aramid coating (the first ceramic coating includes: a second ceramic powder), and ceramic slurry is coated on the other side of the base film (the side not coated with the para-aramid slurry), and the coating is directly dried in an oven (the oven temperature is 60°C, and the drying time is 15s) to obtain a second ceramic coating with a thickness of 1 μm on the base film (the second ceramic coating includes: a second ceramic powder), to obtain a para-aramid coating diaphragm, in which the ratios of para-aramid, gas phase powder, first ceramic powder, second ceramic powder in the first ceramic coating, and second ceramic powder in the second ceramic coating are 2:2:12:42:42 in terms of mass fractions.
[0069] The ceramic slurry for forming the first ceramic coating and the second ceramic coating is the same. The preparation method of the ceramic slurry includes: adding a dispersant to water, stirring for 20 minutes until uniform, adding a second ceramic powder, stirring for 3 hours, sand grinding in a pin-type sand mill for 30 minutes until uniform, adding a thickener, stirring for 20 minutes until uniform, adding a gas-phase pore-forming agent, stirring for 20 minutes until uniform, and finally adding a binder, stirring for 10 minutes until uniform, to obtain a ceramic slurry, wherein the binder is methyl methacrylate, the thickener is an aqueous solution of sodium carboxymethyl cellulose, the concentration of sodium carboxymethyl cellulose in the aqueous solution of sodium carboxymethyl cellulose is 5wt%, the second ceramic powder is barium sulfate, the particle size D90 of the second ceramic powder is 0.4μm, the dispersant is sodium polyacrylate, the gas-phase pore-forming agent is isopropanol, and the ratio of water, dispersant, second ceramic powder, sodium carboxymethyl cellulose, gas-phase pore-forming agent and binder is 22:4:35:5:6:8 by mass.
[0070] The preparation method of the para-aramid slurry comprises: mixing a gas phase powder, a first ceramic powder and a first solvent, stirring for 80 minutes, using a sand mill to sand for 30 minutes until uniform (the speed of the sand mill is 1500r / min), to obtain a solution A, adding the solution A to a para-aramid polymer solution (the viscosity of the para-aramid polymer solution is 3000CP), stirring for 120 minutes until uniform, to obtain a para-aramid slurry, wherein the para-aramid polymer solution comprises: para-aramid and calcium chloride, in parts by mass, the gas phase The ratio of the powder, the first ceramic powder and the para-aramid in the para-aramid polymerization liquid is 4:21:4, the ratio of the gas phase powder and calcium chloride is 3:1 by weight, the ratio of the gas phase powder and the first solvent is 5:95 by weight, the first solvent is N-methylpyrrolidone (NMP) (water content ≤0.5wt%), the gas phase powder is gas phase barium titanate (D90: 0.5μm), the first ceramic powder is boehmite (D90: 0.8μm), and the method for preparing the para-aramid polymerization liquid comprises: The method comprises the following steps: firstly placing calcium chloride in a muffle furnace and calcining at 420°C for 4 hours, mixing the calcined calcium chloride with a second solvent, stirring at 80°C for 6 hours until completely dissolved, cooling to 20°C to obtain a first solution, mixing the first solution, p-phenylenediamine and a modifier, stirring at 15°C for 3 hours until completely dissolved, cooling to -2°C to obtain a second solution, and spraying molten terephthaloyl chloride (solid terephthaloyl chloride is added to a tank and heated to 95°C to obtain molten terephthaloyl chloride) into the second solution. The mixture was stirred while spraying (the spraying speed was 1.5 L / min), and then stirred at 0° C. for 1 hour after spraying to obtain a para-aramid polymerization solution, wherein the ratio of calcium chloride, the second solvent, p-phenylenediamine and the modifier was 8:90:5:3 by weight, the modifier was 1,3-di(4'-aminophenoxy)benzene, the ratio of p-phenylenediamine to molten terephthaloyl chloride was 5:3 by weight, and the second solvent was N-methylpyrrolidone (NMP) (water content ≤0.2wt%).
[0071] Comparative Example 1
[0072] A method for preparing a para-aramid coated diaphragm is substantially the same as Example 1, except that no modifier is added to the para-aramid polymer solution prepared in Example 1. In Example 1, the ratio of calcium chloride, the second solvent and p-phenylenediamine is 5:97:2, and the ratio of p-phenylenediamine to molten terephthaloyl chloride is 2:3, by weight.
[0073] Comparative Example 2
[0074] A method for preparing a para-aramid coated diaphragm, comprising: using an anilox roller to coat the para-aramid slurry in Example 2 on both sides of a base film, extracting (the extraction is sequentially through extracting liquids with extractant concentrations from high to low, the extractant is N-methylpyrrolidone (NMP), the extracting liquids with extractant concentrations from high to low are sequentially a first extracting liquid, a second extracting liquid and a third extracting liquid, the first extracting liquid and the second extracting liquid are each a mixture of an extractant and deionized water, the third extracting liquid is deionized water, the concentration of the extracting liquid in the first extracting liquid is 70wt%, and the concentration of the extracting liquid in the second extracting liquid is 40wt%), drying in an oven at 80°C for 2 min, obtaining a para-aramid coating with a thickness of 1μm on each side of the base film, and obtaining a para-aramid coated diaphragm.
[0075] Comparative Example 3
[0076] A method for preparing a coated diaphragm comprises: using an anilox roller to coat the ceramic slurry in Example 3 on both sides of a base film, drying at 65° C. for 2 min, obtaining a ceramic coating with a thickness of 1 μm on each side of the base film, and obtaining a coated diaphragm.
[0077] Table 1 (Comparison of data of the diaphragms of Examples 1 to 3 and Comparative Examples 1 to 3)
[0078]
[0079] It can be clearly seen from the data in Table 1 that the para-aramid polymer liquid in Comparative Example 1 is prepared by a traditional method without modification, and the ability to wrap the ceramic in the para-aramid slurry is relatively small, resulting in low adhesion of the diaphragm; in Comparative Example 2, the para-aramid slurry is coated on both sides of the base membrane, and the para-aramid does not have enough ceramic to support the diaphragm. Under the test of 130℃*1h, the diaphragm shrinkage rate of Comparative Example 2 is relatively high, and the para-aramid coating on both sides will result in a lower porosity of the diaphragm, making the diaphragm have a higher air permeability, which is not conducive to the shuttling of lithium ions; in Comparative Example 3, ceramic slurry is coated on both sides of the base membrane. Because Comparative Example 3 does not have high-temperature resistant materials, the diaphragm is directly destroyed under the test of 200℃*1h.
[0080] The impedance and ionic conductivity of the separators of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 2.
[0081] Table 2
[0082] Diaphragm Impedance(Ω) Ionic conductivity (mS / cm) Example 1 0.03 1.6 Example 2 0.02 1.7 Example 3 0.02 1.6 Comparative Example 1 0.08 1.3 Comparative Example 2 0.12 0.8 Comparative Example 3 0.03 1.4
[0083] Ionic conductivity mainly tests the rate at which ions shuttle through the diaphragm. As can be seen from Table 2, the ionic conductivities of the diaphragms in Examples 1 to 3 are all relatively high. Both sides of the base membrane of Comparative Example 2 are coated with para-aramid, which increases the impedance of the diaphragm and reduces the porosity of the diaphragm, thereby resulting in lower ionic conductivity of the diaphragm. The ionic conductivities of Comparative Examples 1 and 3 are both lower than those of the embodiment.
[0084] Figure 1 This is a surface scanning electron microscope image of the para-aramid coating of the para-aramid coating membrane in Example 2. Figure 1 It can be seen that after modification, the aramid fiber presents a network structure and still maintains the rigidity of the para-aramid fiber. This structure wraps the ceramic powder more tightly and can enhance the bonding force of the diaphragm.
[0085] Figure 2 The surface scanning electron microscope of the para-aramid coating of the para-aramid coating membrane in Comparative Example 1 shows the Figure 2 It can be seen that the unmodified para-aramid is fibrous, has a poor ability to wrap inorganic particles, and has low adhesion to the underlying PE base film.
[0086] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A para-aramid coated diaphragm, characterized in that: include: A base film, a para-aramid coating and a ceramic coating, wherein the para-aramid coating is connected to one surface of the base film, and the ceramic coating is one or two layers; When the ceramic coating is a layer, the ceramic coating is connected to the other side of the base film or to the para-aramid coating; When the ceramic coating has two layers, the two ceramic coatings are a first ceramic coating and a second ceramic coating, the first ceramic coating is connected to the para-aramid coating, and the second ceramic coating is connected to the other side of the base film; The para-aramid coating comprises para-aramid, gas phase powder and a first ceramic powder, and each layer of the ceramic coating comprises a second ceramic powder. The ratio of para-aramid, gas phase powder, first ceramic powder and the second ceramic powder in each layer of the ceramic coating is (1-4): (1-4): (9-21): (40-80) by mass.
2. The para-aramid coated diaphragm according to claim 1, characterized in that: When the ceramic coating is a layer and the ceramic coating is directly connected to the base film, the ratio of the para-aramid, the gas phase powder, the first ceramic powder and the second ceramic powder in the ceramic coating is (2-4): (2-4): (17-21): (69-79); When the ceramic coating is a layer and the ceramic coating is connected to the para-aramid coating, the ratio of the para-aramid, the gas phase powder, the first ceramic powder and the second ceramic powder in the ceramic coating is (2-4): (2-4): (17-21): (69-79); When the ceramic coating is two layers, the two layers of ceramic coating are a first ceramic coating and a second ceramic coating, the first ceramic coating is connected to the para-aramid coating, and the second ceramic coating is connected to the other side of the base film, and the ratio of para-aramid, gas phase powder, first ceramic powder, second ceramic powder in the first ceramic coating and second ceramic powder in the second ceramic coating is (1-2):(1-2):(9-13):(41-45):(41-44).
3. The para-aramid coated diaphragm according to claim 1, characterized in that: The thickness of the para-aramid coating is 1 to 3 μm.
4. The para-aramid coated diaphragm according to claim 1, characterized in that: The thickness of each ceramic coating layer is 1 to 3 μm.
5. A method for preparing a para-aramid coated diaphragm, characterized in that: include: The ceramic coating is formed by first coating a ceramic slurry and then drying it, and the para-aramid coating is formed by coating a para-aramid slurry, then extracting and forming pores, and finally drying it, wherein the ceramic slurry includes: water, a dispersant, a second ceramic powder, a thickener, a gas-phase pore-forming agent, and a binder, and the thickener is an aqueous solution of sodium carboxymethyl cellulose; in the ceramic slurry: in terms of mass fractions, the ratio of the water, the dispersant, the second ceramic powder, the sodium carboxymethyl cellulose in the thickener, the gas-phase pore-forming agent, and the binder is (15-22): (3-4): (28-35): (2-5): (3-6): (2-8); The para-aramid slurry comprises: gas phase powder, first ceramic powder and para-aramid, and the ratio of the gas phase powder, the first ceramic powder and the para-aramid is (1-4): (9-21): (1-4) by weight.
6. The method according to claim 5, characterized in that The preparation method of the ceramic slurry comprises: mixing water, a dispersant, a second ceramic powder, a thickener, a gas-phase pore-forming agent and a binder until they are uniform to obtain the ceramic slurry.
7. The method according to claim 5, characterized in that The preparation method of para-aramid slurry includes: mixing gas phase powder, first ceramic powder and first solvent until uniform to obtain solution A, mixing solution A and para-aramid polymer liquid until uniform to obtain para-aramid slurry, wherein the para-aramid polymer liquid includes: para-aramid and calcium chloride.
8. The method according to claim 7, characterized in that The viscosity of the para-aramid polymer solution is 800-3000CP.
9. The method according to claim 7, characterized in that: The first solvent is N-methylpyrrolidone, and the ratio of the gas phase powder to the first solvent is (1-5): (90-98) by mass.
10. The method according to claim 7, characterized in that The method for obtaining a para-aramid polymer solution comprises: mixing calcium chloride and a second solvent until uniform, cooling to 5-20°C to obtain a first solution, mixing the first solution, p-phenylenediamine and a modifier until uniform, cooling to -8--2°C to obtain a second solution, spraying molten terephthaloyl chloride into the second solution, stirring while spraying, and stirring at -3-0°C for 1-3h after spraying to obtain a para-aramid polymer solution, wherein, by weight, the ratio of calcium chloride, the second solvent, p-phenylenediamine and the modifier is (2-8): (90-96.4): (2-5): (1-3), the modifier is one or two of 4,4'-diaminodiphenyl ether and 1,3-di(4'-aminophenoxy)benzene, and by weight, the ratio of p-phenylenediamine to molten terephthaloyl chloride is (2-5): (1-3).
Citation Information
Patent Citations
Aramid ceramic diaphragm as well as preparation method and application thereof
CN109509855A
Double-sided coated para-aramid diaphragm and preparation method thereof
CN117820961A
Lithium ion battery separator having high temperature-resistant coating and preparation method therefor
WO2020155001A1
Lithium-ion battery separator and preparation method therefor, and lithium-ion battery
WO2021197134A1
Modified para-aramid polymerization liquid, coating slurry, lithium battery separator and preparation method therefor
WO2022127148A1
Cited By
Para-aramid lithium battery diaphragm and preparation method thereof
CN121307432A
A para-aramid lithium battery separator and its preparation method
CN121307432B